Antagonistic regulation of salt and sugar chemotaxis plasticity by a single chemosensory neuron in Caenorhabditis elegans. - Masahiro Tomioka; Yusuke Umemura; Yutaro Ueoka; Risshun Chin; Keita Katae; Chihiro Uchiyama; Yasuaki Ike; Yuichi Iino (PLoS Genetics, 2023)
The nematode Caenorhabditis elegans memorizes various external chemicals, such as ions and odorants, during feeding. Here we find that C. elegans is attracted to the monosaccharides glucose and fructose after exposure to these monosaccharides in the presence of food; however, it avoids them without conditioning. The attraction to glucose requires a gustatory neuron called ASEL. ASEL activity increases when glucose concentration decreases. Optogenetic ASEL stimulation promotes forward movements; however, after glucose conditioning, it promotes turning, suggesting that after glucose conditioning, the behavioral output of ASEL activation switches toward glucose. We previously reported that chemotaxis toward sodium ion (Na+), which is sensed by ASEL, increases after Na+ conditioning in the presence of food. Interestingly, glucose conditioning decreases Na+ chemotaxis, and conversely, Na+ conditioning decreases glucose chemotaxis, suggesting the reciprocal inhibition of learned chemotaxis to distinct chemicals. The activation of PKC-1, an nPKC ε/η ortholog, in ASEL promotes glucose chemotaxis and decreases Na+ chemotaxis after glucose conditioning. Furthermore, genetic screening identified ENSA-1, an ortholog of the protein phosphatase inhibitor ARPP-16/19, which functions in parallel with PKC-1 in glucose-induced chemotactic learning toward distinct chemicals. These findings suggest that kinase-phosphatase signaling regulates the balance between learned behaviors based on glucose conditioning in ASEL, which might contribute to migration toward chemical compositions where the animals were previously fed.